Pengaruh Social Media Marketing dan Brand Awereness Untuk Meningkatkan Minat Beli Konsumen ( Studi Kasus : Followers Ternak Dimsum Krian ) - Diva Oktaviana; Maya Firnanda; Dwi Novita Sari; Dicky Surya Putra Pradana (Universitas Nusa Nipa Maumere, 2025)
This study looks at how social media marketing interact brand awareness and. Purchase interest is the dependent variable in this study, whereas social media marketing and brand recognition are the independent factors. This study employs a quantitative methodology, employing Google Forms to distribute questionnaires, SPSS 25 for data analysis, and non-probability sampling approaches, namely purposive sampling, to gather data from 112 respondents. The study's findings suggest that brand awareness and social media marketing influence consumers' desire to buy Ternak Dimsum Krian.